PENYULUHAN TENTANG KUALITAS PELAYANAN BAGI TENAGA PARAMEDIK DI PUSKESMAS NAMORAMBE - Diana Sinulingga; Tetty Junita Purba; Nur Mala Sari (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Puskesmas is a primary health care which means it is a health service center that is first visited by community members if they have problems related to their health. Therefore, the Puskesmas was established in a community environment with a work area determined based on applicable regulations. Utilization of health services at the Puskesmas is a process of interaction between consumers who use services and health workers at the Puskesmas as service providers. As a form of service, the service provided must be of quality in accordance with the service quality standards that have been set. Paramedics as health workers in the first line of service at the Puskesmas are expected to have knowledge and understanding related to service quality, and can apply it as much as possible. This counseling is intended to refresh and increase knowledge related to the quality of services for paramedics at the Namorambe Health Center with the hope that this counseling can improve the quality of services in a sustainable manner.